Mega-lakes in the northwestern Tibetan Plateau formed by melting glaciers during the last deglacial. (1st June 2022) - Zhang, Shuai; Zhao, Hui; Sheng, Yongwei; Zhang, Jifeng; Zhang, Junjie; Sun, Aijun; Wang, Leibin; Huang, Lingxin; Hou, Juzhi; Chen, Fahu
Abstract: Rapid lake expansions along with intensive glacier loss in the Tibetan Plateau (TP) in recent decades indicate an enhanced hydrological circulation. Well-preserved paleo-shorelines up to ∼200 m above modern levels in the TP attest to much greater lake expansions in the past and serve as analogues for future lake evolution under climate changes. Mega-lakes in the inner TP, defined by the highest paleo-shorelines, were mainly formed in the early–middle Holocene and are mainly attributed to a high monsoonal rainfall. However, the effect of melting glaciers on the mega-lakes was rarely evaluated, and reliable mega-lake ages are scarce, especially in the northwestern TP (NWTP). We studied six mega-lakes in the NWTP by dating the highest paleo-shorelines using optical dating of multiple and single grains and then reconstructing the paleo-hydrology. The results show that four mega-lakes existed during the last deglacial (16.3–12.6 ka). They had lake levels 53–269 m higher than today and areas up to 7.3 times larger than the modern lakes, containing up to 105.4 km 3 more water. A comparison of mega-lakes across the TP and correlation with independent paleoclimatic records reveal that these mega-lakes attained larger relative sizes (lake area/basin land area ratio) under a dry climate and intensive glacier melting during the last deglacial than the non-glacier-fed mega-lakes that developed in response to the early–middle Holocene rainfall maximum. We suggest that they were formed by melting glaciers, and therefore glaciers had major impacts on long-term lake evolution in the NWTP. Highlights: Post-IR IRSL dating of K-feldspar single-grains determined paleo-shoreline ages. Four mega-lakes developed in the northwestern Tibetan Plateau in the last deglacial. The last deglacial mega-lakes were formed by melting glaciers.